Infant Young Child Feeding Practices in an Indian Maternal–Child Birth Cohort in Belagavi, Karnataka - Shweta Khandelwal (International Journal of Environmental Research and Public Health, 2022)
Poor infant young child feeding (IYCF) practices result in malnutrition, poor psychosocial development, poor school performance and less productivity in later life, thereby perpetuating a vicious cycle. The current study aims to characterize the IYCF practices during the first year of life in a maternal–child birth cohort (DHANI) in Belagavi, Karnataka, India. We collected data from the dyad at birth, 6 and 12 months postpartum. We examined dietary diversity among these infants at 12 months using WHO criteria. A total of 902 live births were recorded, and 878 mother–child pairs completed the 12-month follow up. The overall prevalence of early (within 1 h of delivery) initiation of breastfeeding (EIBF) was 77.9%, and that of exclusive breastfeeding (EBF) at 6 months was 52.4%. At 12 months, most (90%) infants were breastfed, while 39% also received formula. The large majority (94.4%) of infants met minimum meal frequency (MMF), but only 55% of infants were receiving a minimum acceptable diet (MAD). The mean dietary diversity (DD) score was 4.7 ± 1.1. Only 21.9% of infants consumed egg and/or flesh food. A large proportion (33.8%) of infants received no vegetables and/or fruits till 12 months of age. Consumption of sweet beverage was 4.8%, but consumption of ultra-processed foods high in trans-fats, sugars and salt was high (85.8%). High-quality, sustainable and scalable interventions to enhance knowledge and support positive behaviour change for adopting and implementing better IYCF practices may be urgently needed in low- and middle-income group settings to improve diet diversity and overall nutritional intake amongst young children.